Yucatec Maya mothers' ethnotheories about learning to help at home. Issue 4 (14th April 2022) - Alcalá, Lucía; Cervera, María Dolores
Abstract: In most cultures, but particularly among Indigenous communities of the Americas, children help extensively with household work. However, less is known about the role of maternal ethnotheories as cultural organizers of the family environment and children's helping. We explored Maya maternal ethnotheories about children's learning to help in two villages. Mothers reported that children learn by observing and pitching in because they have the will and interest and want to help. Mothers help children by orchestrating the setting, supporting their initiative, but learning must be initiated by children. Results support the view of a Yucatec Maya theory of learning and highlight the relevance of studying maternal ethnotheories. As cultural models, ethnotheories guide the organization of the developmental niche, affording children's learning by observing and pitching in and supporting the emergence of their will and interest. Their study may contribute to further acknowledging and supporting cultural diversity.